Pelatihan Penulisan Buku dan Publikasi Ilmiah Berbasis Riset melalui Pemanfaatan Mendeley bagi Dosen FKIP Universitas Almuslim - Andrian Kaifan; Fauzi A. Gani; Bakhtiar Bakhtiar; Kurniati Kurniati; Almawardi Almawardi; Zulfikar Zulfikar; Khairul Miswar (Universitas Pahlawan Tuanku Tambusai, 2026)
This community service program aimed to enhance academic writing competencies in research-based book writing and scientific publication through the use of Mendeley reference management software. The training was conducted by the Faculty of Teacher Training and Education, Universitas Almuslim, on February 5, 2026, involving 120 lecturers and students. The program covered research-based book development, IMRAD-structured article writing, publication strategies, and hands-on Mendeley training. The methods included lectures, discussions, practical sessions, and satisfaction questionnaire evaluation. The results indicated a very high satisfaction level, with an average score of 4.74 out of 5.00. The training effectively improved participants’ understanding of academic writing structures and reference management skills. Continuous writing clinics are recommended to sustain academic publication productivity.